Natural Compounds Affecting Inflammatory Pathways of Osteoarthritis - Yi Ting Lee; Mohd Heikal Mohd Yunus; Azizah Ugusman; Muhammad Dain Yazid (Antioxidants, 2022)
Osteoarthritis (OA) is the most common type of arthritis and chronic joint disease, affecting more than 240 million people worldwide. Although there are numerous advances in using drugs in treating OA, the use of natural compounds has aroused much interest among researchers due to their safety margin. Recent discovery shows that natural compounds play an extensive role in the oxidative stress signaling pathway in treating OA. Thus, this review summarizes the commonly used natural compounds for treating OA focusing on the oxidative stress signaling pathway and its downstream mediators. Selected databases—such as Scopus, Web of Science, Nature, and PubMed—were used to search for potentially relevant articles. The search is limited to the last 15 years and the search was completed using the Boolean operator’s guideline using the keywords of natural product AND oxidative stress AND osteoarthritis OR natural extract AND ROS AND degenerative arthritis OR natural plant AND free radicals AND degenerative joint disease. In total, 37 articles were selected for further review. Different downstream mechanisms of oxidative stress involved in the usage of natural compounds for OA treatment and anabolic and catabolic effects of natural compounds that exhibit chondroprotective effects have been discussed with the evidence of in vitro and in vivo trials in this review.